THE APPLICATION OF LOCAL WISDOM-BASED LKPD TO IMPROVE SOCIALSCIENCE (IPS) LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Munjiatun; Zufriady; Non Syafriafdi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of students’ learning outcomes through the application of LKPD (Students’ Worksheet) based on local wisdom. Indonesian local character is essential to be taught to students including through teaching materials in the form of LKPD based on local wisdom that can be used as a reference in the teaching and learning process. LKPD is one of the teaching materials in which there are all the basic activities carried out by students in order to maximize their understanding and formation of basic skills based on the indicators of competency achievement. The research used is Classroom Action Research (PTK) using the research design of Kemmis and Mc. Taggart model. The research was conducted at SDN 189 Pekanbaru. The research subjects involved 20 fourth-grade students. The research uses quantitative data analysis. Descriptive statistical data collection techniques were carried out through observation, interviews, and evaluation tests at the end of the cycle. Based on the results of cycle I to cycle II, there was a significant improvement with an achievement percentage of 75%. 35% of students have not achieved the KKM standard yet. The students’learning outcomes in social science learning through the application of LKPD learning media based on local wisdom increased. The students’ average score increased from the initial reflection of 62.25 with the highest score at 80 and the lowest score from 35 to 74.00. Thehighest score was 90 and the lowest score was 40 in cycle I. Even though it was not appropriate with the KKM that had been determined in cycle II, it increased to 80.00 with the highest score of 90 and the lowest score of 55.